Rare bird documentation form for Glaucous Gull at Lock and Dam 15 at Davenport, 1983 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1983)
Rare bird documentation form for two Glaucous Gulls at Lock and Dam 15 at Davenport in Scott County, IA on December 18, 1983. Epson - sheet feed